1996
DOI: 10.1200/jco.1996.14.8.2206
|View full text |Cite
|
Sign up to set email alerts
|

In vivo purging with high-dose cytarabine followed by high-dose chemoradiotherapy and reinfusion of unpurged bone marrow for adult acute myelogenous leukemia in first complete remission.

Abstract: This approach offers a relatively high DFS rate to adult patients with AML in first CR. The results of this study are similar to those achieved with allogeneic BMT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
17
0
2

Year Published

1998
1998
2004
2004

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(23 citation statements)
references
References 40 publications
4
17
0
2
Order By: Relevance
“…Prior HDAC may have contributed to delayed engraftment. Stein et al 20 reported engraftment data which are similar to ours using unpurged bone marrow collected after post-remission therapy including HDAC. Alternatively, the use of HDAC remission induction therapy may have had a beneficial effect.…”
Section: Discussionsupporting
confidence: 72%
“…Prior HDAC may have contributed to delayed engraftment. Stein et al 20 reported engraftment data which are similar to ours using unpurged bone marrow collected after post-remission therapy including HDAC. Alternatively, the use of HDAC remission induction therapy may have had a beneficial effect.…”
Section: Discussionsupporting
confidence: 72%
“…13 Mobilization of PBPCs by the use of high-dose chemotherapy alone or in combination with growth factors, such as GM-CSF or G-CSF, may produce a sufficient number of progenitor cells to ensure early engraftment and serve as a means of reducing potential leukemia cell contamination. 14,15 In order to assess the long-term outcome of myeloablative preparative conditioning without the high TRM and mortality of either allogeneic transplantation or purged autologous PBPCs, we evaluated the risk of relapse, LFS, and overall survival in 129 patients with AML in CR1 treated with high-dose chemoradiotherapy followed by the infusion of autologous PBPCs procured after high-dose consolidation chemotherapy as a form of in vivo purging. This large group of patients, followed over a 10-year period, represents a population of adult leukemia patients unrestricted on the basis of age or prognostic features.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the rate of severe toxicity (most particularly infectious complications) after EMA chemotherapy was relatively high. Toxicity of WHO grade more than 2 following EMA therapy was observed in 23% of cases and did not compare favorably to the 8% previously reported by Stein et al 22 with high-dose cytarabine in AML from all subtypes. Failure of harvesting could be exceptionally related to prior treatment by ATRA and early intensification chemotherapy.…”
Section: Discussionmentioning
confidence: 65%